Ultra-high strength and high toughness 24CrNiMo alloy steel fabricated by laser powder bed fusion and subsequent quenching - Qing Wang; Deyin Kong; Zhihui Zhang (Journal of Materials Research and Technology, 2023)
A nearly fully dense grade 24CrNiMo alloy steel with superior comprehensive performance was fabricated by laser powder bed fusion (LPBF) under optimum laser parameters and subsequent quenching treatment was applied. The effect of quenching temperatures on microstructure evolution and mechanical properties of the LPBF 24CrNiMo parts were first systematically characterized and analyzed. The results demonstrated that the microstructure of LPBF 24CrNiMo steel (submicron grain size of 2.99 μm on average) was mainly constituted by block and stripe granular bainite containing twin substructure and θ-Fe3C carbides with no macroscopic segregation and anisotropy. After quenching, with the increase of quenching temperature from 800 to 1000 °C, the microstructure gradually changed from the acicular ferrite to martensite, finally to tempered martensite. The fine grains, the numerous twins were retained and the nanoscale carbides η-Fe2C were precipitated after quenching at 850 °C, simultaneously obtaining ultra-high mechanical properties including the hardness, yield strength, ultimate tensile strength and elongation were 446 HV and 1380 MPa, 1517 MPa, 13.8 %, respectively as well as the surface scratch resistance improved about 25 %. As quenching temperatures varied to 1000 °C, the mechanical properties lowered due to the coarsening and uneven distribution of the grain and θ-Fe3C carbides as well as the decrease in the number of twins. The improved mechanical properties via quenching treatment was attributed to phase transformation strengthening, grain refinement strengthening and precipitate strengthening.